Enacting new visions: headteachers’ preparatory work amidst revised language arts syllabi - Susanne Duek; Anna Lindholm; Jenny Uddling (Education Inquiry)
Swedish schools offer two parallel subjects for the national majority language: Swedish (SWE) and Swedish as a second language (SSL). Several reports have shown disparities across schools in the country concerning the organisation of Swedish instruction for students with first languages other than Swedish. As headteachers are responsible for the organisation and quality of the instruction, this article aims to study headteachers’ descriptions of providing Swedish instruction to second-language students in anticipation of the introduction of new compulsory school curricula (Lgr22) with revised syllabi. By applying theories of policy enactment, the study examines factors enabling or hindering the enactment and headteachers’ interpretation of the new syllabi for SWE and SSL. Interviews were conducted with nine compulsory headteachers during the preparations for the new curriculum. The preparation for these curricula highlighted a range of problems within the school subject of SSL and headteachers had already taken measures to address certain shortcomings during the preparatory work. These measures may potentially contribute to increased quality and equity for students. The results of the study provide insights into the challenges and opportunities that headteachers experience in relation to the enactment of the syllabi, as well as shed light on the challenges associated with SSL.